Characteristics and Neural Correlates of Emotional Behavior during Prefrontal Seizures. Issue 6 (6th October 2022) - Singh, Rinki; Giusiano, Bernard; Bonini, Francesca; Lagarde, Stanislas; Brockington, Alice; Trébuchon‐Dafonseca, Agnès; Bartolomei, Fabrice; McGonigal, Aileen
Abstract : Objective: This study was undertaken to characterize clinical expression and intracerebral electroencephalographic (EEG) correlates of emotional expression during prefrontal epileptic seizures. Methods: We performed a descriptive analysis of seizure semiology in patients explored with stereo‐EEG (SEEG) for pharmacoresistant prefrontal epilepsy, using a semiquantitative score for seizure‐related emotional behavior. Two independent observers scored occurrence and intensity of objective emotional features (face/body movements/vocalization/overall appearance), testing interobserver reliability. Intracerebral electrophysiological changes were documented. Cluster analysis and principal component analysis (PCA) compared behavioral signs with neural SEEG correlates. For each patient, the clinical and anatomoelectrophysiological scores were established, based on a prototypical emotional seizure. Results: Forty‐two patients (469 seizures) were included. Interobserver correlation for emotional signs was satisfactory (kappa = 0.6–0.8). Prevalence of any subjective and/or objective ictal emotional phenomena was 79% (33/42); objective emotional signs occurred in 27 of 42 subjects (64%). Negatively valenced emotional semiology (ictal feeling of fear, defensive and/or aggressive behaviors) was much more prevalent than positively valenced, prosocial behaviors. Cluster analysis and PCA identified 4 groups with different occurrence of emotional signs and cerebral correlates. Two main clusters of negatively valenced behavior were identified: "active threat response, " associated with seizure organizations involving posterior orbitofrontal cortex, anterior cingulate, and dorsolateral and/or ventrolateral prefrontal cortex; and "passive fear, " associated with amygdala, other mesial temporal structures, and posterior orbitofrontal cortex. Interpretation: Emotional behaviors, especially fear/threat response, are common in prefrontal seizures, reflecting the role of the prefrontal cortex in emotional control. Different cortical seizure localizations were associated with "passive fear" and "active threat response" seizure behaviors at the group level. ANN NEUROL 2022;92:1052–1065